Development of Assessment Instrument Schoology Assisted to Assess Student Learning Outcome on The Newton’s Motion Law Material - I Dewa Putu Nyeneng; Undang Rosidin; Ni Luh Putu Suwartika Eka Putri (Jurnal Pembelajaran Fisika, 2020)
The purpose of this study was to develop an assessment instrument aided by schoology in Newton's motion material. This research development refers to the research design by Lee and Owens with statistics consisting of analysis, design, development, implementation, evaluation. The results obtained from this study are the validity of the assessment instruments that have been developed very high with an average score of material expert tests 0.90, construct expert tests 0.94, and language expert tests 0.91, very high validity criteria, readability test 0.90 with a very good category. The assessment instruments that have been developed can already be used to assess student learning outcomes. This can be seen through the results of small group trials that produce a Cronbach alpha value of 0.886 which is included in the category of instruments with high reliability. Students respond positively to online exams through schoology. The conclusion of this study produced a valid assessment instrument to assess student learning outcomes with the help of schoology.Keywords: Assessment instrument, Learning outcome, Schoology useDOI: http://dx.doi.org/10.23960/jpf.v8.n1.202003